AB0734 Prevalence and co-occurrence of autoantibodies in blood donors. (23rd January 2014) - Jung, W.; Prüßmann, J.; Recke, A.; Rentzsch, K.; Juhl, D.; Henschler, R.; Müller, S.; Lamprecht, P.; Schmidt, E.; Csernok, E.; Görg, S.; Stöcker, W.; et al.
Abstract : Background: Incidence of autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis, has continuously increased over the past decades [1]. Different autoimmune diseases seem to co-occur at greater than expected rates [2] and patients are prone to develop autoantibodies targeting antigens apparently unrelated to the underlying autoimmune disease. Autoantibodies can be found prior to the clinical onset of some autoimmune diseases and may be also detected in healthy individuals [3], whereas it is not clear if different autoantibodies co-occur in healthy individuals. Objectives: To address this issue, prevalence of different autoantibodies was determined in healthy blood donors and tested for possible co-occurrence. Methods: 5, 455 blood donors were assayed and validated for presence of antinuclear antibodies (ANA) showing a SLE-associated immunofluorescence (IF) pattern and antigen specificity was determined by immunoblotting. To establish an independent control group, antibodies associated with rheumatoid arthritis (anti-CCP), autoimmune thyroiditis (anti-TPO), pernicious anemia (anti-PCA), bullous pemphigoid (anti-BP180/BP230), pemphigus (anti-Dsg1/3) and granulomatosis with polyangiitis (ANCA) as well as ANA were detected in additional 999 and 369 (TPO, PCA) blood samples, respectively. All validated ANA positive samples were also screened for these antibodies. Results: ANA prevalence amounted to 5.62% (titer 1:100), 3.66% (1:320), 1.53% (1:1, 000), 0.17% (1:3, 200) and 0.02% (1:10, 000). At least one Ab against SLE-specific antigens was detected in 77 (1.19%) samples, and frequency of detection correlated with increasing titers. Anti-CCP antibodies were detected in 1.3%, anti-TPO in 4.6%, anti-PCA in 1.1%, anti-BP180/BP230 in 0.6%, anti-Dsg1/3 in 0.1%, and ANCA in 0.3% of samples. Prevalence of anti-CCP (OR 3.2), anti-TPO (OR 2.4) and anti-Dsg1/3 antibodies (OR inf.) was significantly higher in ANA positive samples. Conclusions: Our results demonstrate co-occurrence of ANA with autoantibodies to distinct antigens apparently unrelated to SLE in healthy blood donors, suggesting a common control of natural autoantibody production. Some antibodies like ANCA did not show this correlation, indicating that additional antigen dependent, immunogenetic and/or environmental factors could play a role in triggering their production. References: NEJM 347:911. Journal of Autoimmunity 33(3-4):197. NEJM 349:1526. Disclosure of Interest: None Declared